MCF-7 and its Multidrug Resistant Variant MCF-7/ADR Overcome TNF Cytotoxicity through Prevention of Reactive Oxygen Species Accumulation - Morteza Ghandadi; Javad Behravan; Samira Biabani; Sara Abbaspor; Fatemeh Mosaffa (Tabriz University of Medical Sciences, 2019)
Background: Signal transduction of numerous cytokines and growth factors are mediated by reactive oxygen species (ROS). Tumor necrosis factor-α (TNF-α) have stimulated accumulation of ROS in various in vitro studies. MCF-7 and its Adriamycin resistant variant MCF-7/ADR are resistant against TNF-α cytotoxicity. Role of ROS in the resistance of MCF-7 and MCF-7/ADR cells was investigated. Methods: ROS accumulation and viability in MCF-7 and MCF-7/ADR after TNF-α exposure was evaluated using 2',7'-dichlorofluorescein diacetate (DCFH-DA) as a fluorescent probe and 3-[4, 5-dimethylthiazol-2-yl]-2, 5 diphenyltetrazolium bromide (MTT) cytotoxicity assay respectively. Results: ROS level did not change significantly after TNF-α exposure. Induction of ROS accumulation along with TNF-α treatment sensitized these cells to TNF-α toxicity. Conclusion: It can be concluded that lack of ROS accumulation following TNF-α exposure is involved at least by part in the resistance of MCF-7 and its drug resistant derivative MCF-7/ADR cells to TNF-α cytotoxicity.